2022
DOI: 10.2196/37611
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Artificial Intelligence in Health Care and Social Services in Australia: Findings From a Methodologically Innovative National Survey of Values and Attitudes (the AVA-AI Study)

Abstract: Background Artificial intelligence (AI) for use in health care and social services is rapidly developing, but this has significant ethical, legal, and social implications. Theoretical and conceptual research in AI ethics needs to be complemented with empirical research to understand the values and judgments of members of the public, who will be the ultimate recipients of AI-enabled services. Objective The aim of the Australian Values and Attitudes on AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…We found that some stakeholders had the view that bias does not exist in healthcare AI, based on the epistemic belief that these knowledge systems are not biased. People taking this view are incorrect as a matter of fact: algorithmic bias has been demonstrated across domains including healthcare, 33 social welfare, 34 legal systems 35 and finance. 36 In healthcare, studies continue to demonstrate the persistence of racial disparities in diagnostic imaging that predates AI applications.…”
Section: Discussionmentioning
confidence: 99%
“…We found that some stakeholders had the view that bias does not exist in healthcare AI, based on the epistemic belief that these knowledge systems are not biased. People taking this view are incorrect as a matter of fact: algorithmic bias has been demonstrated across domains including healthcare, 33 social welfare, 34 legal systems 35 and finance. 36 In healthcare, studies continue to demonstrate the persistence of racial disparities in diagnostic imaging that predates AI applications.…”
Section: Discussionmentioning
confidence: 99%
“…We used the shortened version of the questionnaire as a reference survey to produce weights for the non-probability sample that account for characteristics that influence people's propensity to participate in the online panel. A more detailed description of the data collection and weighting methodology is provided in Isbanner et al [14]. For this analysis, we report on results from the weighted non-probability sample using data obtained from the full questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Others are analysing linked data to improve evidence‐based policy around the social and health outcomes of early childhood experience, which carries long term health implications 6 . Other applications include the monitoring and improvement of prescription practices, 7 and the development of artificial intelligence (AI)‐supported medical technologies 8 . In addition to universities and learned academies, the benefits of data integration are widely recognised across Australian Government agencies, so that considerable investment and reform have been underway to strengthen data integration capacities to support research and innovation, create efficiencies and private–public partnerships, and accelerate data‐driven decision making within policy and routine modes of government 9…”
mentioning
confidence: 99%
“…In countries that are further advanced in data integration, such as the United Kingdom, private sector access to health data has provoked public controversy, indicating that Australia should be proactive in developing strategies to regulate and share data from and with the private sector in ways that allow innovation while also aligning with broadly shared visions of the public good 12,13 . The imperative to keep human decision making visible, and data systems transparent and accountable, is a major concern globally 8,10,13‐15 . Many agree that public confidence in the secondary uses of health data requires a social license 12,13,15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation